Secondary Dengue Infection Complicated by Hemophagocytic Lymphohistiocytosis: A Case Report - Dominique D. Davis; Saffett Guleryuz; Yehuda Galili; Pablo A. Bejarano (Case Reports in Infectious Diseases)
Hemophagocytic lymphohistiocytosis is a fatal hyperinflammatory disorder in which CD8+ cytotoxic T-cells, natural killer cells, and macrophages destroy hematopoietic cells and vital organs. Viral infections, such as Epstein–Barr virus, are known to cause secondary hemophagocytic lymphohistiocytosis in adult patients. However, despite its rarity, dengue virus has been identified to potentially cause hemophagocytic syndrome, which is associated with significant mortality and morbidity. Herein, we present a case report of a 52-year-old male patient who presented with fevers, worsening non-bloody copious diarrhea, excessive fatigue, and nausea and vomiting. He was known to have sickle cell trait. A diagnosis of hemophagocytic lymphohistiocytosis was confirmed with a liver biopsy, accompanied by elevated ferritin levels (33,539 ng/mL), IL-2R levels (5944.2 pg/mL), thrombocytopenia (49 k/μL), anemia (hemoglobin and mean corpuscular volume of 7.3 g/dL and 77.3 fL), and elevated bilirubin (total bilirubin of 3.2 mg/dL). In addition, elevated IgG and IgM antibodies determined reinfection with dengue virus. The administration of dexamethasone, etoposide, and additional supportive medications was initiated. Despite all efforts, the patient’s neurological status declined, and the patient died. In this case, dengue-induced hemophagocytic lymphohistiocytosis is a worrisome and challenging diagnostic condition, primarily due to the similarities between the symptoms of hemophagocytic lymphohistiocytosis and those of dengue hemorrhagic fever. Treatment delay may be an inevitable consequence. Differentiating between dengue hemorrhagic fever and dengue-induced hemophagocytic lymphohistiocytosis requires evaluating clinical, laboratory, and biopsy findings. The role of the sickle cell trait is unknown in the presentation.